Nanoparticle Reinforcement in Elastomeric Polyethylene Composites Under Tensile Tests - Zapata-Ramirez, P (Elsevier Ltd, 2016)
Two ethylene-1-butene thermoplastic elastomer copolymers were melt mixed with different nanometric fillers such as: multi-walled carbon nanotubes (CNT), thermally reduced graphite oxide (TrGO), and spherical metal nanoparticles. The effect of both the kind and amount of nanoparticles on the tensile mechanical behavior of the matrices was evaluated focusing on the elastic modulus. The low elastic modulus of the pure elastomeric polymers, with values of 50 and 9 MPa depending on the amount of comonomer, can be largely increased by adding nanoparticles although the reinforcement was conditioned by the matrix and kind of filler. For instance, while CNT increased the elastic modulus of the stiffer matrix with a maximum of 80%, this property increased 4,3 times as compared with the pure matrix when added to the softer matrix. Noteworthy, TrGO particles rendered even larger improvements with composites based on the softer matrix reaching values as high as 7 times the modulus of the pure sample at concentrations less than 10 vol%. Spherical metal nanoparticles otherwise rendered outstanding improvements in the elastic modulus (around 60%) at concentrations as low as 2 vol%. These results were explained by micromechanical models stressing the relevance of both the aspect ratio and the mechanical properties of the particle agglomerates rather than of the isolated particles. © 2016 Elsevier Ltd